Actividades lúdicas para niños con discapacidades intelectuales a través de los juegos acuáticos en la fundación de niños especiales San Miguel de Salcedo - Raura Chicaiza, Myriam Marlene (2016)
In the development of this research was applied an investigative methodology based on a quantitative approach, through numerical measures of certain aspects of the phenomena studied; also of concrete cases to reach a general description; like research level, it allowed diagnose and know about teaching practice in children with intellectual disabilities through aquatic activities.This research began by the lack of use on ludic activities for children with intellectual disabilities through aquatic games, through surveys made by parents who allowed later their analysis, interpretation, and data tabulation with the conclusions and recommendations mentioned. Further, this work is based and structured in the use of ludic activities that incise in the accumulation of practical learning, significant too with the children with intellectual disabilities through ludic activities, they can learn to develop their skills and capabilities through aquatic games. Finally, this research will take place with the help of children, parents and authorities of the foundation, thus enabling to contribute with the development as intellectual as physical in the main beneficiaries like are children with intellectuals disabilities, so children can act reflectively, and solve the problems by critically thinking, making intelligent use of what they know and overcome challenges and difficulties efficiently and effectively way.